Liver CT Perfusion Imaging as a Non-Invasive Method for Assessing Hemodynamics of the Hepatic Parenchyma in Patients with Fibrosis and Cirrhosis as a Result of Chronic Viral Hepatitis C - G. A. Stashuk; Ya. G. Moysyuk; D. Ya. Smirnova; O. V. Sumtsova (Вестник рентгенологии и радиологии)
Objective: to determine whether liver computed tomography (CT) perfusion imaging can assess hemodynamics in patients with fibrosis and cirrhosis as a result of chronic viral hepatitis C (CVHC). Subjects and methods. The prospective study conducted at the Department of Radiation Diagnosis, M.F. Vladimirsky Moscow Regional Research and Clinical Institute, enrolled 61 patients with liver fibrosis and cirrhosis as a result of CVHC, of whom 26 patients had received antiviral therapy (AVT) and achieved a sustained virological response (SVR) at 24 weeks after the end of treatment. All the patients underwent liver CT perfusion imaging on a 256-slice Philips ICT computed tomography scanner (Netherlands). The parameters of arterial, portal, general perfusion and hepatic perfusion index were measured in each patient in his/her liver segments III, VII, and VIII, by calculating the slope of a curve. Results. The values of perfusion parameters in patients who had undergone AVT and attained SVR and who had received no specific treatment were compared with those in the fibrosis, compensated, subcompensated, and decompensated liver cirrhosis groups. In the liver fibrosis group, the patients who had achieved SVR after AVT had higher portal and total perfusion values than those who had received no specific treatment (p = 0.001 and p = 0.002; respectively). In the same group, the liver perfusion index was higher in the patients who had not undergone AVT than in the treated patients (p = 0.028). The values of total perfusion were statistically significantly higher in patients with compensated liver cirrhosis who had attained SVR after AVT than in the untreated patients (p = 0.008). In the decompensated liver cirrhosis group, portal perfusion after specific treatment was higher than in the non-AVT group (p = 0.012). The subcompensated liver cirrhosis group showed no statistically significant differences when comparing the values of liver perfusion parameters depending on the availability of treatment. Conclusion. Liver CT perfusion imaging cannot give an idea of how the hemodynamics of liver tissue changes in the presence of fibrosis and cirrhosis in patients with CVHC after AVT.